Blood tests and fair competition: the biathlon experience - Manfredini, F.; Carrabre, J. E.; Litmanen, H.; Zhukovskaja, L.; Malagoni, A. M.; Dal Follo, D.; Haberstroh, J. (International Journal of Sports Medicine, 2003)
In recent years, some international sports federations have introduced blood testing procedures that can lead to suspension from competition for athletes whose haematologic values exceed certain established limits. In 1994 the International Biathlon Union initiated a three-phase blood testing program to safeguard athletes' health and ensure fair competition. The first phase, lasting three years, was aimed at measuring the haematocrit values of biathletes in order to determine statistically acceptable limits for participation in competition. The second phase, lasting four years, consisted of pre-race testing for an increasing number of athletes and suspension from competition for those whose haematocrit values exceeded 52 % for males and 48 % for females. The results of this second phase (third phase now in progress) are reported. Progressive increases have been made in the numbers of countries examined, athletes tested, and tests performed. This retrospective study reveals a reassuring trend in average values for haematocrit and haemoglobin in the entire study population, a minimal number of athletes with excessive values and a consequent low risk of false positive results, an acceptable incidence of relatively high values (50 % for males and 45 % for females), and constant non-elevated haematological profiles for elite athletes. The variability in individual haematocrit levels among all biathletes with a minimum of four observations during the four-year period is also evaluated and discussed.